Readiness of Wait-Listed Black Patients to Pursue Live Donor Kidney Transplantation - Rodrigue, James R. (Prog Transplant, 2014)
CONTEXT: For adults with end-stage kidney disease, live donor kidney transplantation (LDKT) yields superior outcomes over long-term dialysis and deceased donor kidney transplantation. However, blacks receive LDKT at a much lower rate than adults of any other race or ethnicity. OBJECTIVE: To examine the LDKT readiness stage of blacks on the transplant waiting list and its association with LDKT knowledge, concerns, and willingness. DESIGN: Cross-sectional analysis of baseline data from a randomized controlled trial to improve knowledge and reduce concerns about LDKT. PATIENTS AND SETTING: One hundred fifty-two black patients on the kidney transplant waiting list at a single transplant center in the northeastern United States. MAIN OUTCOMES: LDKT readiness stage, knowledge, concerns, and willingness to talk to others about living donation. RESULTS: Sixty percent of patients were not considering or not yet ready to pursue LDKT, while only 11% had taken action to talk to family members or friends about the possibility of living kidney donation. Patients in later stages of LDKT readiness (i.e., had talked to others about donation or were preparing to do so) had significantly more knowledge (p<0.001), fewer concerns (p=0.002), and more willingness (p=0.001) to talk to others about living donation than those in earlier readiness stages. CONCLUSIONS: The large percentage of blacks who are in the earlier stages of LDKT readiness may account for the low rate of LDKT in this patient population at our transplant center. Innovative and tailored LDKT educational strategies for black patients are needed to help reduce racial disparities in LDKT.